2014
DOI: 10.1177/230949901402200205
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Injection of Tranexamic Acid to Reduce Blood Loss after Total Knee Arthroplasty

Abstract: Intra-articular administration of TXA is effective in reducing blood loss after TKA, without increasing the risk of VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…The TXA also decreased the number of the packed red blood cell transfusion per patient. Routes of administration of TXA are different in the literature such as intra-articular, 17 intravenous, and oral, 18 with no literature showing one route to be superior to another.…”
Section: Discussionmentioning
confidence: 99%
“…The TXA also decreased the number of the packed red blood cell transfusion per patient. Routes of administration of TXA are different in the literature such as intra-articular, 17 intravenous, and oral, 18 with no literature showing one route to be superior to another.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 41 articles are included in this article as either background or supportive material (n ¼ 25) 2, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][25][26][27][28][29][30][31] or as the quantitative meta-analysis (n ¼ 16). 1,3,23,24,[32][33][34][35][36][37][38][39][40][41][42][43] The study selection is shown in the PRISMA flowchart (►Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Eight of the 16 studies included in the meta-analysis were blinded randomized controlled trials, CEBM Level I, 32,34,36,[38][39][40]42,43 1 study was a nonblinded randomized controlled trial, CEBM Level II, 41 and the remaining 7 studies were case-controlled trials, CEBM Level III 1,3,23,24,33,35,37 (►Table 1). Sample sizes ranged from 24 to 373 patients receiving unilateral TKAs, a total of 2,610 patients (1,339 IA-TXA and 1,271 placebo) were enrolled in the 16 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations